A case of severe soft tissue infection due to Streptococcus tigurinus diagnosed by necropsy in which genomic analysis was useful for clarifying its pathogenicity. Issue 5 (23rd March 2018) - Yoshizawa, Hidenori; Motooka, Daisuke; Matsumoto, Yuki; Katada, Ryuichi; Nakamura, Shota; Morii, Eiichi; Iida, Tetsuya; Matsumoto, Hiroshi
Abstract : Post‐mortem detection of pathogenetic microorganisms in severe infectious death is significantly important for diagnosing the cause of death as well as for public health. However, it is difficult to recognize whether a microorganism detected from post‐mortem materials is truly pathogenic or not. We report a case of severe soft tissue infection due to Streptococcus oralis subsp. tigurinus ( S. tigurinus ), a recently reported species, in which whole‐genome analysis was performed to clarify its pathogenicity. A 46‐year‐old woman had died with symptoms of a severe infectious disease. A post‐mortem examination was performed by a medical examiner. The external findings suggested a soft tissue infection; subsequently, pathological specimens sampled by necropsy revealed findings compatible with necrotizing fasciitis. In the post‐mortem bacterial test, S. tigurinus was detected from the localized autopsy sample. Whole‐genome sequencing was performed to analyze its pathogenicity and detected a strain of S. tigurinus with genetic determinants that were specific and unique to its highly virulent strains as a result of gene annotation. Utilizing various technologies, such as whole‐genome sequencing, may be a powerful tool for diagnosing the cause of infectious death accurately and safely.